The informal sector in the structure of the national economy: Simulation and evaluation - Lizina, Olga; Bistyaykina, Dinara; Ermakova, Eka; Badokina, Tatyana; Solovyeva, Tatiana (Journal of Eastern European and Central Asian Research (JEECAR), 2020)
The research into the shadow economy has scientific and practical value. Any state is interested in evaluating the size of the shadow economy as it affects the goals and priorities of the country’s development. This study presents a model for evaluating the shadow economy in the Russian Federation. The authors developed and analyzed an approach to measuring the shadow economy based on factor analysis and a MIMIC model. The study features the factor analysis of the official statistics for Russia over the period from 1992 to 2019, with more than 150 indicators characterizing different spheres of the life of the country. The authors determined the factors affected by the shadow economy, built a MIMIC model on this basis, and estimated the size of the shadow economy in Russia. Assessing the size of shadow activity is important for analyzing economic development and the impact of government regulations on the shadow sector